Continued decline in genetic diversity among wild cheetahs (Acinonyx jubatus) without further loss of semen quality. (August 2016) - Terrell, Kimberly A.; Crosier, Adrienne E.; Wildt, David E.; O'Brien, Stephen J.; Anthony, Nicola M.; Marker, Laurie; Johnson, Warren E.
Abstract: As a well-studied felid with limited genetic diversity, the cheetah ( Acinonyx jubatus ) has shaped much of the scientific debate surrounding inbreeding depression. The species survived a population bottleneck ~ 12, 000 years ago and was extirpated from > 75% of its historical range in the last century. Modern cheetahs produce poor-quality semen, a presumed manifestation of inbreeding depression. Within Felidae, a positive association between genetic diversity and semen quality is well supported by pedigree data and inter-species comparisons. However, this relationship has never been examined among individual cheetahs. Furthermore, whether ongoing population declines are exacerbating inbreeding depression in wild or captive cheetah populations is unknown. Using 12 microsatellite markers, we evaluated the relationship between heterozygosity and reproductive traits among wild ( n  = 54) and captive ( n  = 43) male cheetahs born from 1976–2007. We tested the hypotheses that genetic diversity has declined over the last ~ 30 years and is positively correlated with semen quality/breeding success in the cheetah. Findings revealed that genetic diversity has decreased in the wild, but not captive, population. Unexpectedly, heterozygosity was lower in proven versus unproven breeders and did not correlate with semen quality. A small proportion of all males (< 10%) produced relatively high quality ejaculates, with sperm traits similar to those of non-inbred felid species. These data suggest a more complex relationship between inbreeding and male cheetah reproductive traits than previously appreciated. Intensive management of captive cheetahs appears to be minimizing inbreeding, whereas the continued erosion of genetic diversity in wild males is of conservation concern. Highlights: Heterozygosity has declined among wild Namibian cheetahs over the last 30 years. Intensive genetic management has minimized further inbreeding in captive cheetahs. Heterozygosity did not correlate with semen quality in either population. Genetic diversity was lower in proven versus unproven breeders housed in captivity.